Nitrogen Dioxide Optical Sensor Based on Redox-Active Tetrazolium/Pluronic Nanoparticles Embedded in PDMS Membranes - Esteban Araya-Hermosilla; Rodrigo Araya-Hermosilla; Francesco Visentin; Francesco Picchioni; Andrea Pucci; Virgilio Mattoli (Chemosensors, 2022)
Anthropogenic toxic vapour and gases are a worldwide threat for human health and to the environment. Therefore, it is crucial to develop highly sensitive devices that guarantee their rapid detection. Here, we prepared redox-switchable colloids by the in-situ reduction of 2,3,5-triphenyl-2H-tetrazolium (TTC) into triphenyl formazan (TF) stabilised with Pluronic F127 in aqueous media. The colloids were readily embedded in polydimethylsiloxane (PDMS) to produce a selective colour-switchable membrane for nitrogen dioxide (NO2) detection. We found that the TTC reduction resulted in the production of red-coloured colloids with zeta potential between −1 to 3 mV and hydrodynamic diameters between 114 to 305 nm as hydrophobic dispersion in aqueous media stabilised by Pluronic at different molar concentrations. Moreover, the embedded colloids rendered highly homogenous red colour gas-permeable PDMS elastomeric membrane. Once exposed to NO2, the membrane began to bleach after 30 s due to the oxidation of the embedded TF and undergo a complete decolouration after 180 s. Such features allowed the membrane integration in a low-cost sensing device that showed a high sensitivity and low detection limit to NO2.